Perancangan Alat Pendeteksi Suhu Tubuh dan Sanitasi Tangan Otomatis Pada SMP Negeri 1 Mekar Baru - Roihan, Ahmad; Jawahir, Jawahir; Alfariji, Holid (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
Early detection of COVID-19 transmission relies heavily on taking a body temperature reading. The use of touch-based methods for measuring core body temperature increases the risk of infection at SMPN 1 Mekar Baru. Data collecting, block diagrams, analyses, prototypes, and tests are all used in this study. The GY-906 sensor and the Infrared Obstacle sensor are used in the creation of an automatic hand sanitizer and thermometer, respectively; the Node Mcu V3 processes the data. The 20x4 Lcd layer is next in line to display the data. The goal of this study is to develop an automatic body temperature detector that can send data to the officer's smartphone by way of the blynk app. Automatic controls, monitoring, and alerts eliminate the need for a human officer to be present.